ANALISIS KOREKSI FISKAL DALAM RANGKA PERHITUNGAN PPH BADAN PADA PT. BANK PERKREDITAN RAKYAT NUSA UTARA - Kalangie, Brilliant Joy Leonardo; Nangoi, Grace B.; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
The income statement is something that is very important in the financial statements. In the income statement presents income (revenue), costs (expenses) and income (profit / losses) a company within a certain time period or periods. Income statement itself is also a financial statement must be derived from the accounting system, both made in accordance with provisions in the Law - Tax Law as well as those in charge based financial Accounting Standards (GAAP). Basically, both of these things (Law - Tax Law and the Financial Accounting Standards) regulate the same thing that is about how much the amount of the charge to the consumer. However, the fiscal correction, we can find something different. This difference is what happens when the accounting of income in measuring too low and unnatural because of special treatment that favor the occurrence of this. Fiscal correction itself is a correction or adjustment must be done before calculating the taxpayer's income tax for corporate taxpayers and tax personal use of accounting in calculating taxable income. The aim of this study was to determine the fiscal correction is done by PT. Rural Bank Nusa North in order calculating corporate income tax. This study took place at the office of PT. Rural Bank Nusa North. The company is located at Jl. Nusantara No. 98 Complex Bersehati Market Manado. The object of this study is the income / loss of PT. Rural Bank Nusa North. This study uses descriptive qualitative research because in practice, such as data, analysis and interpretation of the meaning and the data obtained. In this study, the author will study the financial statements of the profit-rui in 2013 and 3014 were obtained from the company. Then analyzed whether fiscal reconciliation process made are correct and in accordance with regulations Regulations - Tax regulations prevailing in Indonesia at this time. The results showed that the company has made a statement profit / loss of commercial accordance with the applicable accounting standards, and has made statements of income / tax loss properly in accordance with the tax laws and regulations. So it can be taxable income of PT. RB Nusa North, then calculate the income tax in accordance with the calculation of the applicable tax rate on taxable income (PKP) from PT. RB Nusa North.